PENEGAKAN HUKUM PEMERINTAH TERHADAP PENAMBANGAN EMAS TANPA IZIN (PETI) DI KECAMATAN CERENTI KABUPATEN KUANTAN SINGINGI TAHUN 2015 - Marselon "; Raja Muhammad Amin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Case Gold Mining Without Permission (PETI) which are prevalent in the province of Riau, one along the river Cerenti Cerenti Subdistrict Regency Kuantan Singingi. In addition to mining activities that are not equipped with a permit, also the gold mining activities destroy nature and ecosystems and devastating the lives of people who live along the river. The problem in this research is how the government law enforcement against Gold Mining Without Permission (PETI) in District Kuantan District Cerenti Singingi the Year 2015? The purpose of this study is to investigate to determine the law enforcement government against Gold Mining Without Permission (PETI) in District Cerenti Regency Kuantan Singingi 2015 and barriers in law enforcement government against Gold Mining Without Permission (PETI) in District Cerenti Regency Kuantan Singingi 2015. in this study, researchers used a descriptive research with a qualitative method approach. This research is located in the district of Kuantan District Cerenti Singingi. For the research informants using purposive sampling techniques. Data collection techniques used were observation, interviews and documentation. To examine the issues raised in this study, the authors analyze the data using descriptive methods.The results of this study can be concluded that the government's handling of law enforcement against Gold Mining Without Permission (PETI) in District Kuantan District Cerenti Singingi 2015 is running as it should. In the framework of the rule of law, the general handling procedures together with other common criminal case. Kuantan district police Singingi inhibiting factor in dealing with criminal assault Gold Mining Without Permission include: (1) lack of public awareness (2) of miners in the back-up by oknumyang not responsible (3) the suspect fled.Keywords: Law Enforcement, Gold Mining Without Permission (Peti)